MEMORI KOLEKTIF : PERISTIWA MANDOR BERDARAH BAGI MASYARAKAT KALIMANTAN BARAT - Khofifah nur rahmah; Rhoma dwi yuliantri; Novi Herawati; Gilar Wullida; Ni Luh Wika Kristiani; Muhammad Lingga (STKIP Singkawang, 2025)
This study aims to explore how the people of West Kalimantan maintain and transmit collective memory of this tragedy through oral traditions, rituals, and memorial sites such as the Makam Juang Mandor. This study uses a qualitative approach with in-depth interviews as the main data collection technique. The research informants consisted of the victims' families, community leaders, local historians, the general public, and students involved in commemoration efforts and studies of the event. In-depth interviews were conducted with a semi-structured guide to explore their personal experiences and views related to the Bloody Mandor event, the role of oral traditions, and annual commemoration ceremonies. In addition, observations of commemoration activities and visits to historical sites were also used to enrich the data. The data obtained were analyzed using thematic analysis techniques, which identified key themes such as the meaning of the Bloody Mandor event in the context of local identity and how the community maintains collective memory. The results of this study indicate that collective memory not only functions as a tool to remember history, but also strengthens the social identity and cultural solidarity of the people of West Kalimantan. However, challenges arise in passing on this history to the younger generation who are increasingly exposed to modern narratives through digital media. This research contributes to the understanding of historical consciousness and identity of the Indonesian nation, as well as the importance of integrating local historical narratives into national discourse